Prototype of Laboratory Scale Centrifuge for Gum Crude Palm Oil (CPO) Separate - Solehudin An Nur; Mursalin Mursalin; Rahmadi, Apri; Irawan, Doddy; Julianto, Eko (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study concentrates on the design and construction of a laboratory-scale centrifuge for the separation of gum from crude palm oil (CPO). The extraction of gum from CPO is essential in the palm oil sector to guarantee that the finished product adheres to quality standards and is safe for consumption. We engineered the prototype centrifuge to accommodate six 600-mL bottles and achieve a maximum rotational speed of 1400 rpm. The design procedure utilised Autodesk Inventor software for CAD modelling and computations to ascertain the centrifugal force, power capacity, and shaft diameter. The process of manufacturing entailed cutting and shaping stainless steel into the necessary components, subsequently followed by drilling and milling operations for mounting points and interfaces. We implemented surface treatment to augment corrosion resistance and elevate visual appeal. The assembling procedure encompassed component integration, motor incorporation, and control system configuration. The experimental configuration involved centrifugal testing utilising 600-mL glass bottles with time intervals of 10, 20, 30, and 40 minutes at an average rotational speed of 924 rpm. The experiment showed that the centrifuge worked well to separate the gum and other contaminants from the CPO. The best separation happened after 40 minutes of centrifugation.